Representation of Feminism in the Film Hati Suhita : Islamic Perspective - Nur Afwi Aulia; Jumriani (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
This study aims to analyze the representation of feminism in the film Hati Suhita from an Islamic perspective using John Fiske's semiotic model. As a cinematic work that explores the themes of women, religion, and culture, Hati Suhita presents the complexity of women's roles within both domestic and public spheres. John Fiske's semiotic theory is employed to deconstruct the meanings embedded within the film's visual and narrative symbols through three levels of coding: reality, representation, and ideology. This qualitative research analyzes 36 selected scenes (screenshots) examined in depth. The findings reveal that the film portrays female characters, especially Alina Suhita, as representations of devout yet resilient and empowered Muslim women. She is depicted not only as obedient in the domestic sphere but also as a capable leader who actively contributes to the social realm through her involvement in managing a pesantren (Islamic boarding school). Feminist values such as independence, perseverance, female solidarity, and resistance to gender injustice are presented in the film without disregarding Islamic principles. At the ideological level, the film subtly critiques patriarchal norms embedded in society through a soft and religious lens. In conclusion, Hati Suhita successfully represents feminism within an Islamic framework by employing strong, symbolically rich cinematic elements with a spiritual tone. These findings significantly contribute to studying media, gender, and Islam in Indonesian culture.